A simplified and reproducible ex vivo model of cold and ischemia-reperfusion injury - Lele Zhang; Mingjie Ding; Ying Zhu; Zhiping Yan; Wenzhi Guo (Liver Research)
Both cold stress and ischemia-reperfusion injury significantly contribute to poor prognosis after liver transplantation (LT). However, limited animal models incorporating both stimuli hinder the advancement of transplant-related research. Here, a simplified and reproducible isolated perfused liver model is established to simulate the stresses experienced by livers maximally during transplantation. We provide a detailed protocol for a straightforward technique that requires 20–30 min for harvesting, 24–48 h for static cold storage (SCS), and 2 h for normothermic machine perfusion (NMP) to induce LT-like stresses in the liver. Hepatic injury from SCS and NMP (LT-like stresses) is evaluated using three types of parameters. The pH values and hepatic enzyme levels of cold preservation solutions and perfusate serve as dynamic indicators of hepatic injury. Bile production and portal venous resistance directly reflect liver function, whereas pathological analysis visually illustrates the location and extent of injury. This animal model eliminates the influence of hemodynamic and immune factors, yielding highly reproducible results, and is strongly recommended as a standardized animal model for inducing LT-like stresses.